2012
DOI: 10.5849/forsci.10-057
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Deadwood Using Harmonized National Forest Inventory Data

Abstract: Abstract:Deadwood plays an important role in forest ecological processes and is fundamental for the maintenance of biological diversity. Further, it is a forest carbon pool whose assessment must be reported for international agreements dealing with protection and forest management sustainability. Despite wide agreement on deadwood monitoring by national forest inventories (NFIs), much work is still necessary to clarify definitions so that estimates can be directly compared or aggregated for international repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 18 publications
1
36
0
3
Order By: Relevance
“…Findings similar to ours have been reported by and Woodall and Liknes (2008). Rondeux et al (2012) assessed the impact of using different threshold diameters in the range from 10 to 20 cm and found that a 20 cm threshold decreased the volumes of dead wood with 30%. In this case, most of the data emanated from temperate forests.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Findings similar to ours have been reported by and Woodall and Liknes (2008). Rondeux et al (2012) assessed the impact of using different threshold diameters in the range from 10 to 20 cm and found that a 20 cm threshold decreased the volumes of dead wood with 30%. In this case, most of the data emanated from temperate forests.…”
Section: Discussionsupporting
confidence: 77%
“…Increasing the threshold diameter to 20 cm, corresponding to the national definition used in some central European countries (e.g. Rondeux et al 2012), our estimate was 7.3 m 3 ha -1 , i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Thomas scale (Thomas 1979) (Table 2) was used to assess the degree of decomposition of standing dead biomass and a 4-point harmonized scale (Rondeux et al 2012) (Table 3) for lying biomass and stumps.…”
Section: Stumps -Panjevimentioning
confidence: 99%
“…Hence, determining the forest floor (litter) and mineral soil organic carbon stocks as well as the influence of forest management on soil carbon stocks forms a critical part of decision-making processes (Jandl et al, 2007;Tonon et al, 2011). Deadwood is recognized as an essential component in forest stands, particularly with regard to biodiversity conservation and ecosystem functioning, and it represents an important forest carbon pool (Rondeux et al, 2012). Forest inventories provide data to estimate this carbon pool (e.g., Harmon & Marks, 2002) and although deadwood estimates for Mediterranean forests are scarce, the importance of deadwood in carbon storage and the influence of forest management have gained prominence in recent years (e.g., Lombardi et al, 2008;Herrero et al, 2010;Paletto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%